Iron deficiencies: focus on teenage girls - T.M. Vasil'eva; I.N. Zakharova; A.L. Zaplatnikov; N.G. Sugyan; E.V. Shirdanina; E.A. Doroshina; L.S. Serikova; I.D. Maikova; Kuznetsova O.A; A.S. Vorob'eva; Radchenko E.R; L.V. Goncharova; et al. (LCC «Medicine-Inform», 2019)
T.M. Vasil'eva1,2, I.N. Zakharova1, A.L. Zaplatnikov1,3, N.G. Sugyan1,2, E.V. Shirdanina2, E.A. Doroshina1, L.S. Serikova1, I.D. Maykova3, O.A. Kuznetsova3, A.S. Vorob'eva3, E.R. Radchenko3, L.V. Goncharova3, N.V. Gavelya3 1Russian Medical Academy of Continuous Professional Education, Moscow,  Russian Federation 2City Children Outpatient Department No. 133, Moscow, Russian Federation 3Z.A. Bashlyaeva City Children Clinical Hospital, Moscow, Russian Federation Aim: to improve the efficacy of iron deficiency treatment in teenage girls by their early diagnosis and rational treatment. Patients and Methods: complete blood count was performed in 2,303 teenage schoolgirls aged 14-17 years (mean age 16.3±0.6 years) who underwent routine annual medical examination. Whole capillary blood was tested. Reduced hemoglobin concentration (less than 120 g/l) was anemia diagnostic criterion in teenage girls. Hypochromic anemia was verified in color index less than 0.85 and mean corpuscular hemoglobin (MCH) less than 26 pg. In some girls (n=133) with verified isolated hypochromic red blood cells but in the lack of anemia and microcytosis, serum iron, total iron-binding capacity, serum ferritin, and transferrin saturation were measured. Results: hypochromic anemia was diagnosed in 8.3% of teenage girls. In 96.8% of them, anemia was mild. In 133 teenage girls with verified hypochromic red blood cells but no anemia, latent iron deficiency was diagnosed in 20.3% of cases. Preliminary results of mild iron-deficiency anemia treatment in 19 teenage girls (mean age 14.7±0.5 years) using Tardyferon demonstrate its good tolerability and high clinical laboratory efficacy. After 4 weeks of the treatment, hemoglobin concentration has increased by 10.7±0.3 g/l (р<0.05). No adverse side effects were reported. Conclusions: our findings demonstrate that the algorithm described in this paper should be followed to improve the diagnosis of iron deficiencies. Keywords: anemia, hypochromic RBCs, teenage, iron deficiencies, iron-deficiency anemia, latent iron deficiency, iron preparations, Tardyferon. For citation: Vasil'eva T.M., Zakharova I.N., Zaplatnikov A.L. et al. Iron deficiencies: focus on teenage girls. Russian Journal of Woman and Child Health. 2019;2(3):206-212.